Solution of the nonlinear equation for isothermal gas flows in porous medium by Trefftz method - Uściłowska, Anita; Kołodziej, Jan A. (Computer Assisted Methods in Engineering and Science, 2006)
This paper presents numerical solution to a problem of the transient flow of gas within a two-dimensional porous medium. A method of fundamental solution for space variables and finite difference method for time variable are employed to obtain a solution of the non-linear partial differential equation describing the flow of gas. The inhomogeneous term is expressed by radial basis functions at each time steps. Picard iteration is used for treating nonlinearity.